Chronic Testicular Pain- A Review of Literature - Mallik, Ashraf Uddin; Islam, Md waliul; Islam, MS; Islam, Md shahidul; Islam, AHM Manjurul; Hossain, Anwar; Hossain, Zinnat (Bangladesh Journal of Urology, 2020)
Objective: To review the current understanding of testicular pain, possible etiology and the available treatment options. Materials and Methods: A literature search was made for abstract, original and review articles in the Medline, hand-searched relevant reference lists and conference proceedings and medical text book using the word “testicular pain” and orchialgia to find out possible etiology, understanding of testicular pain and treatment options. Results: After literature search, it has found that management of testicular pain sometimes a challenging work for an Urologist. Management differs for the original etiology and for testicular and extra testicular causes. Sometimes symptomatic treatment improve the quality of life but in few cases surgery is mandatory for relieve of pain. Conclusions: Management of chronic testicular pain depends on careful assessment of the causes. Relieve of symptoms is not always possible with analgesic only, in that case blockade of the spermatic cord will be helpful. Decision for surgery should not be undertaken quickly for there is no guarantee that there will always be resolution of pain For that reason patient should be counseled accordingly. Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.18-20